The Impact of digitization on the religious sphere: televangelism as an example - Shaimma El Naggar (Indonesian Journal of Islam and Muslim Societies, 2014)
Over the past few decades, televangelism has emerged as one important media phenomenon, inter alia, among Muslim communities. As a phenomenon, televangelism is interesting in many respects; it is a manifestation of the phenomenon of "info-tainment" as televangelists integrate entertainment features such as sound effects and music in their sermons. It is also a manifestation of the rise of the celebrity culture as televangelists have become 'media celebrities' with thousands of hundreds of fans and followers on social media networks. Thematically, this study is divided into two main sections. First. I delineate the characteristics of televangelism as a novel form of religious expression in which televangelists adopt a modern style and use colloquial language; and in which televangelists present religion as a source of individual change. I have argued that these features seem to have granted televangelists popularity particularly among Muslim youth who view televangelism as a new form of religious expression that is modern in appearance and relevant to their everyday lives.The study has further highlighted the importance of digital media technologies in popularizing televangelists' programmes and sermons. Drawing on two case studies of popular televangelists, namely Amr Khaled and Hamza Yusuf, the study has shown that televangelists draw on a plethora of digital media tools to extend the visibility of their programmes including websites and social media networks. The study has found that televangelists' fans play an important role in popularizing televangelists' programmes. Moreover, the study relates televangelism to the rise of digital Islam. The study has argued that digitization and the increase of literacy rates have changed the structure of religious authority in the twenty first century, giving rise to new voices that are competing for authority. Having provided an explanatory framework for the phenomenon of televangelism, the study moves in the second section to critique televangelism as an 'info-tainment' phenomenon.Drawing on Carrette and King's Selling Spirituality, one issue that the study raises is the extent to which televangelism fits into the modern form of 'spiritualities'. Rather than being a critical reflection of the consumer culture, modern spiritualities seem to 'smooth out' resistance to the hegemony of capitalism and consumerism. I have proposed that it is through a content-related analysis of televangelists' sermons that one can get a nuanced understanding of how the discourses of particular televangelists can possibly relate to dominant (capitalist) ideologies, how structures of power are represented in their discourses and what their texts may reveal about the socio-historical contexts of Muslims in the twenty first century.